Empowering farmers through learning: Establishing field demonstrations in the upper west region of Ghana under the excellence in agronomy initiative - Jizorkuwie, Abdul-latif Baamonyor; Ofosu-Ampong, Kingsley; Akpatsu, Isaac Boatey; Abera, Wuletawu (2024)
Empowering Farmers Through Learning: Establishing Field Demonstrations in the Upper West Region of Ghana under the Excellence in Agronomy Initiative